Group investigation inquiry online learning model for empowering students' metacognitive abilities and creative thinking - Sriyanti I. A Salmanu; Kristin Sangur; Sintje Liline; Dominggus Rumahlatu; Mery Pattipeilohy (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Numerous educational models have been developed to enhance students' aptitudes in online learning. Therefore, this study aimed to analyze the effect of the group investigation inquiry online learning model (GINO) on the metacognitive and creative thinking abilities of students in Senior High Schools (SHS) in Ambon, Indonesia. The method employed a pretest-posttest control group design, with a sample comprising 116 students from Senior High Schools 1, 4, and 12 Ambon. Validity and reliability tests were also conducted to measure metacognitive abilities and creative thinking. Furthermore, the data analysis encompassed descriptive and inferential approaches, employing ANCOVA. The results showed that the GINO learning model effectively enhances the metacognitive abilities and creative thinking of SHS students in Ambon (p=0.000<α=0.05). To foster a distinct online learning environment, the model was subjected to modifications in its learning stages through the integration of the group investigation learning model and inquiry strategies, providing valuable variations in the learning process. This research contributes to showing how varied learning is very important in providing a more interesting learning climate compared to conventional learning carried out by teachers and this learning model can be applied to other concepts in learning.Abstrak. Berbagai model pembelajaran telah dikembangkan untuk meningkatkan kemampuan siswa dalam pembelajaran daring. Oleh karena itu, penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran group investigation inquiry online (GINO) terhadap kemampuan berpikir metakognitif dan kreatif siswa pada Sekolah Menengah Atas (SMA) di Ambon, Indonesia. Metode penelitian ini menggunakan desain kelompok kontrol pretest-posttest, dengan sampel yang terdiri dari 116 siswa dari SMA 1, 4, dan 12 Ambon. Uji validitas dan reliabilitas juga dilakukan untuk mengukur kemampuan metakognitif dan berpikir kreatif. Selanjutnya, analisis data menggunakan statistik deskriptif dan inferensial, dengan menggunakan ANCOVA. Hasil penelitian menunjukkan bahwa model pembelajaran GINO secara efektif meningkatkan kemampuan metakognitif dan berpikir kreatif siswa SMA di Ambon (p=0.000<α=0.05). Untuk menumbuhkan lingkungan belajar online yang berbeda, model ini mengalami modifikasi dalam tahapan pembelajarannya melalui integrasi model pembelajaran investigasi kelompok dan strategi inkuiri, sehingga memberikan variasi yang berharga dalam proses pembelajaran. Penelitian ini berkontribusi untuk menunjukkan bagaimana pembelajaran yang bervariasi sangat penting dalam memberikan iklim pembelajaran yang lebih menarik dibandingkan dengan pembelajaran konvensional yang dilakukan oleh guru dan model pembelajaran ini dapat diterapkan pada konsep-konsep lain dalam pembelajaran.